ANALISIS MOTIVASI ECOPRENEUR DALAM MEWUJUDKAN GREEN ECONOMY PADA PEMILIK USAHA NATURAL DYE FASHION RONSAGA - Masitha Fahmi Wardhani; Diana Puspitasari; Risanda Alirastra Budiantoro (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2021)
The presence of Natural Dye Fashion Ronsaga with its founders Mr. Wahyu and Ms. Dewi as ecopreneurs is needed to support improving the welfare and social equality of the community while reducing environmental damage. One of the strategic steps taken is to encourage industry and business actors to commit and behave in an environmentally friendly manner. This study aims to determine what factors motivate an ecopreneur in running his business, ecopreneur motivation theory. This research uses a qualitative method by describing and describing the empirical reality behind the phenomenon. The population in this study was carried out by observations and interviews aimed at the owner of Natural Dye Fashion Ronsaga. The results showed that there was a match between the research objectives and the theory used. There are five things that motivate Pak Wahyu in running his business as an ecopreneur, namely in the form of green values, gaps in the market, make a living, be their own boss, and passion.